A highly sensitive ratiometric optical cryothermometer using a new broadband emitting trivalent bismuth singly activated Ba2ZnSc(BO3)3 microcrystal. Issue 40 (24th September 2021) - Huang, Shixiang; Zhang, Feng; Wu, Zhangyue; Fu, Ying; Li, Chao
Abstract : A new Ba2 ZnSc(BO3 )3 :Bi 3+ phosphor that exhibits excellent temperature-dependent color variation and good temperature response sensitivity has been reported. Abstract : Motivated by the growing demand for noncontact temperature sensing in cryogenic environments, the development of a high performance low temperature optical thermometer has become more and more urgent. Herein, we demonstrate a new broadband emitting bismuth singly activated Ba2 ZnSc(BO3 )3 optical thermometric material that exhibits a remarkable temperature-dependent emission color variation and a good low temperature sensing performance. First, Bi 3+ doped Ba2 ZnSc(BO3 )3 phosphors were successfully synthesized by a high-temperature solid-state reaction. Upon excitation at 320 nm, the emission spectra of Ba2 ZnSc(BO3 )3 :Bi 3+ cover almost the entire visible region from 350 to 720 nm because of the multiple crystallographic sites occupied by Bi 3+ ions, which have been verified by structure analysis and time-resolved emission spectroscopy. Interestingly, the temperature dependent emission characteristics indicated that the thermal quenching phenomena of Bi 3+ at different lattice sites were different, resulting in a very sensitive emission color variation from orange to cyan. Further analysis indicated that these Bi 3+ doped luminescent materials showed a good performance in temperature sensing over a wide temperature range from 10 to 374 K, with a maximum relative sensitivity of 3.076% K −1 at 210 K. Finally, this study provides a new perspective for the design of superior thermosensitive phosphors, aimed toward non-rare earth ion doped thermosensitive phosphors for optical cryothermometry applications.